Improving Students’ Speaking Skill Through Task Based Language Teaching At Mandalika University Of Education - Sugianto Sugianto; Kamarudin Kamarudin; Ahmad Hanan (JUPE : Jurnal Pendidikan Mandala, 2020)
The article was written to show how the task based language teaching as a language teaching method can improve students’ speaking skill at Mandalika University Of Education. The research was conducted by involving the first semester students of english department Mandalika University of education. The type of the research was classroom action research in which task based language teaching was a method adopted to improves the students’ speaking skill. Collecting the research data, the researcher used two kinds of research instruments. Speaking tests were used to measure the improvement on students’ speaking skill, meanwhile observation was conducted to define how the task based language teaching improves the students’’ speaking skill. The research was concluded to has some significant improvements on students’ speaking skill proved by deviation scores gained between first cycle and second cycles of the research in which the task cycles, interesting topics of discussion, and activities through the task based language teaching method were considered as factors which significantly affected students’ speaking skill improvement.